Perceptions and Challenges of Engineering and Science Transfer Students From Community College to University in a Chinese Educational Context - Lau, Yui-yip; Tang, Yuk Ming; Yiu, Nicole S. N.; Ho, Ceci Sze Wing; Kwok, Wilson Yeung Yuk; Cheung, Kin (Frontiers in Psychology, 2022)
Transfer students have encountered different challenges unfolding in their transition from community college to university study. However, limited research has been conducted to explore their discipline-specific challenges. To address this gap, in this study three engineering and science faculties were selected from which to collect data through 35 in-depth interviews with transfer students, followed by a thorough thematic analysis. On the basis of the thematic analysis, we identified three main themes: 1) “shifted the focus of study” (three sub-themes: (i) academic excellence in community college; (ii) future career in the university; and (iii) university life); 2) “encountered challenges in the transition” (four sub-themes: (i) non-matching programme articulation; (ii) heavy study workload and its associated consequences and (iii) non-specific administration arrangement and support from university); and 3) “students’ voices to enhance learning experiences” (four sub-themes: (i) modify the study duration; (ii) improve programme articulation; (iii) improve social adjustment and (iv) overseas exchange). The results of this study indicate the challenges faced by transfer students in their transition from community college to university and have implications for universities to design and implement appropriate strategies to prepare for the future.